If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + -3k = 6 Solving 5h + -3k = 6 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3k' to each side of the equation. 5h + -3k + 3k = 6 + 3k Combine like terms: -3k + 3k = 0 5h + 0 = 6 + 3k 5h = 6 + 3k Divide each side by '5'. h = 1.2 + 0.6k Simplifying h = 1.2 + 0.6k
| 4x-(x-4)=16 | | O(24)=2n-1 | | 6y=2y+20 | | 4v^2-29v+7=0 | | 25x+50y=300 | | -5x-4+7x=12 | | 0.8x+.18-.4x=.3(x+.2) | | -6(x+1)-11=14+5 | | 17x+200=900 | | 6x+37=15-62 | | 9x-4x=-20 | | 3(-4)x=0 | | x+2=6x-5 | | -4+19x=61 | | n-5.9n-6.5=-0.5n+2.3 | | T=5t+5w | | 5k-12=3k | | 4x+2x+8=32 | | 8-8x=21-5x | | 172=32-w | | 15.025= | | 11x-7-8x=35 | | 2x-5(x-3)=-7+2x+2 | | 10x+15=71 | | (7a^3-6a^2+5a+6)+(5a^3+9a^2-8a+3)= | | 35-5x=x-9 | | 2x+80=70 | | 2.5x+76.5=12x-9 | | 2w^2+w-48=0 | | 2log(x)=log(14-5x) | | 8(6x-3)= | | 8u-6=8u-11 |